THE EXPERIENCES OF SM3T TEACHERS: CONSTRUCTING TEACHER IDENTITY IN THE BORDERLAND DISCOURSES - Gracia Vica Ade Nugraheni (LET: Linguistics, Literature and English Teaching Journal)
This study focuses on the experiences of SM3T teachers in constructing teacher identity in the borderland discourses. Teacher identity construction is a dynamic process. One of the aspects constructing teacher identity is borderland discourse. In short, borderland discourse is the intersection between oneself as a personal and as a professional. The participants of this research were five teachers who have experienced SM3T program. SM3T is a program held by the government in Indonesia. It stands for Sarjana Mengajar Terdepan, Terluar, Tertinggal. In order to find out SM3T teachers’ experiences and beliefs about constructing teacher identity in the borderland discourses, the researcher used mixed methods which were combination between quantitative and qualitative. The researcher used close-ended questionnaire and also in-depth interview in order to gather further information.This study aimed to find out the borderland discources faced by the SM3T teachers and the solution to cope them. This study revealed that most of the teachers faced borderland discources during SM3T program.